2022
DOI: 10.1177/09637214221121302
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Nurture of Callous-Unemotional Traits

Abstract: Callous-unemotional (CU) traits, a risk factor for psychopathy, delineate youths with relatively low empathy and guilt, and identify youths with high risk for chronic and severe antisocial behavior (e.g., rule breaking, aggression). We describe work identifying nature and nurture influences on the development of CU traits. Additionally, we clarify the relationship between CU traits and psychopathy, highlight potential misinterpretations of findings on influences of “nature” versus “nurture,” and discuss treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The concept of psychopathy is complex and key debates are in no danger of rapid resolution (Miller & Lynam, 2012; Skeem & Cooke, 2010). Knowledge accumulation is iterative and slow, but insights and tools from personality science can help to accelerate the process (see Hyde & Dotterer, 2022 on callous and unemotional traits). No one need start fresh, however, should they desire to adopt some or all of our suggestions.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of psychopathy is complex and key debates are in no danger of rapid resolution (Miller & Lynam, 2012; Skeem & Cooke, 2010). Knowledge accumulation is iterative and slow, but insights and tools from personality science can help to accelerate the process (see Hyde & Dotterer, 2022 on callous and unemotional traits). No one need start fresh, however, should they desire to adopt some or all of our suggestions.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…We revisit this below, but for now what does exist suggests that Psychopathy Checklist -Revised scores over a 2-year period were less stable in adolescence (r = 0.31) than adulthood (r = 0.71; Cauffman et al, 2016). Heritability estimates were around 50% for rank order stability across individuals in 'callous-unemotional (CU) traits'-a construct related to psychopathy, particularly the domain of 'meanness' or 'antagonism' (see Figure 1 in Hyde & Dotterer, 2022 for a depiction of the overlap)-spanning approximately 5-year periods (Moore et al, 2019). Henry et al (2018) reported evidence that genetic factors at age 7 continued to capture portions of variation in CU traits at ages 9, 10, and 12 years old.…”
Section: Sources Of Variancementioning
confidence: 99%
See 1 more Smart Citation
“…Later twin research found that MZ twins receiving harsher treatment from parents showed a great frequency of CU traits, relative to their co-twins; however, not all studies concurred. Hyde and Dotterer (2022) noted that warm parenting can mitigate CU traits in children, illustrative of gene × environment interactions.…”
Section: Twin Study Of Callous-unemotional Traitsmentioning
confidence: 99%
“… There is a well‐established association between clinically low levels of empathy (i.e., callous unemotional traits often present in conduct disorder; Hyde & Dotterer, 2022) and alcohol problems (Wymbs et al, 2012). We are referring to normative variation in empathy levels as assessed, for example, by the Interpersonal Reactivity Index questionnaire (Davis, 1980).…”
mentioning
confidence: 99%